2016
DOI: 10.1161/strokeaha.116.013869
|View full text |Cite
|
Sign up to set email alerts
|

Altered Expression of Long Noncoding RNAs in Blood After Ischemic Stroke and Proximity to Putative Stroke Risk Loci

Abstract: Background and Purpose Though peripheral blood mRNA and microRNA change following ischemic stroke, any role for long noncoding RNA (lncRNA), which comprise most of the genome and have been implicated in various diseases, is unknown. Thus, we hypothesized that lncRNA expression also changes following stroke. Methods lncRNA expression was assessed in 266 whole-blood RNA samples drawn once per individual from ischemic stroke patients and matched vascular risk factor controls. Differential lncRNA expression was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
99
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(106 citation statements)
references
References 54 publications
3
99
0
Order By: Relevance
“…In the lncRNA-miRNA-mRNA regulatory network, KEGG pathway analysis indicated that lncRNAs may regulate relative mRNAs via "PI3K-Akt signaling pathway", "p53 signaling pathway", "AMPK signaling pathway", "MAPK signaling pathway", "Wnt signaling pathway", and "TGF-beta signaling pathway" to perform functions. LncRNAs are dysregulated in several diseases, such as obesity, ischemic heart failure, moyamoya disease, and stroke [12][13][14][15]. Dykstra-Aiello explored the lncRNA expression profile of IS and stroke risk loci by using human peripheral blood obtained from American and Canadian subjects; the results identified 299 and 97 differentially expressed lncRNAs in males and females, respectively (P < 0.005, |FC| > 1.2) [12].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
See 2 more Smart Citations
“…In the lncRNA-miRNA-mRNA regulatory network, KEGG pathway analysis indicated that lncRNAs may regulate relative mRNAs via "PI3K-Akt signaling pathway", "p53 signaling pathway", "AMPK signaling pathway", "MAPK signaling pathway", "Wnt signaling pathway", and "TGF-beta signaling pathway" to perform functions. LncRNAs are dysregulated in several diseases, such as obesity, ischemic heart failure, moyamoya disease, and stroke [12][13][14][15]. Dykstra-Aiello explored the lncRNA expression profile of IS and stroke risk loci by using human peripheral blood obtained from American and Canadian subjects; the results identified 299 and 97 differentially expressed lncRNAs in males and females, respectively (P < 0.005, |FC| > 1.2) [12].…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…LncRNAs are dysregulated in several diseases, such as obesity, ischemic heart failure, moyamoya disease, and stroke [12][13][14][15]. Dykstra-Aiello explored the lncRNA expression profile of IS and stroke risk loci by using human peripheral blood obtained from American and Canadian subjects; the results identified 299 and 97 differentially expressed lncRNAs in males and females, respectively (P < 0.005, |FC| > 1.2) [12]. Affymetrix GeneChip Human Transcriptome 2.0 arrays (> 40, 000 lncRNAs and > 245, 000 coding transcripts) were used to detect significantly altered lncRNAs in the Dykstra-Aiello study; meanwhile, we used Arraystar Human LncRNA Microarray v4.0 (40, 173 lncRNAs and 20, 730 coding transcripts) in the present study.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…One study demonstrated abnormal expression of lncRNAs in stroke, some of which bound to co-repressors of REST, a transcription factor that affects stroke-mediated cell death [5]. LncRNAs are potential novel biomarkers that should be explored further for use in the diagnosis, treatment and prognosis of stroke [6]. Metastasisassociated lung adenocarcinoma transcript 1 (MALAT1) is a highly abundant lncRNA that exerts anti-inflammatory and anti-apoptotic roles in the brain microvasculature to reduce ischemia in the cerebral vasculature [7].…”
Section: Introductionmentioning
confidence: 99%
“…They can also be transcribed bidirectionally within 100 bp of their promoters (Fig. C) . Future studies of lncRNAs may enable new approaches to understanding, diagnosis, and treatment of neurological disorders …”
Section: Types Of Ncrnasmentioning
confidence: 99%